ARAH POLITIK HUKUM LINGKUNGAN DI INDONESIA - Marhaeni Ria Siombo (Masalah-Masalah Hukum, 2013)
Abstract The participation of the government of Indonesia in various international conventions on the environment, does not necessarily indicate that the Indonesian government's commitment to implement the concept of Sustainable Development is in accordance with what has always been proclaimed the world. When viewed from the perspective of product legislation at the level of legislation, it is good enough. In the days of the Orde Baru (Soeharto) Repelita concept to the government reform (SBY) concept of environmentally sound development is explicitly normative. The problem is at the level of implementation. Too many interests including political and bureaucratic corruption that undermined the possibility of being the cause of the implementation of legal norms that have been made, is running slow. And often the blame is the imperfection of the product of legislation, not on how the government makes the rules implementative implementation and strongly implement the mandate of the legislation that has been made. So that natural resource wealth owned Indonesian really used as much as possible to increase the welfare of the people.   Keywords: sustainable development, political law, government policy. Abstrak Keikutsertaan pemerintah Indonesia dalam berbagai konvensi internasional di bidang lingkungan, tidak selalu menunjukkan bahwa komitmen pemerintah Indonesia untuk menerapkan konsep Pembangunan Berkelanjutan adalah sesuai dengan apa yang selalu dicanangkan dunia. Bila dilihat dari perspektif undang-undang produk di tingkat undang-undang, itu cukup baik. Pada zaman Orde Baru (Soeharto) sampai pada pemerintah (SBY) konsep pembangunan berwawasan lingkungan secara eksplisit normative, sudah memadai. Permasalahannya adalah pada tingkat implementasi. Terlalu banyak kepentingan politik dan termasuk korupsi  birokrasi yang menggerogoti kemungkinan menjadi penyebab pelaksanaan norma-norma hukum yang telah dibuat, berjalan lambat. Dan sering menyalahkan  ketidaksempurnaan produk undang-undang, bukan pada bagaimana pemerintah membuat aturan pelaksanaan implementatif dan  melaksanakan amanat undang-undang yang telah dibuat. Sehingga kekayaan sumber daya alam yang dimiliki Indonesia benar-benar digunakan sebanyak mungkin untuk meningkatkan kesejahteraan rakyat. Kata kunci: pembangunan berkelanjutan, politik hukum, kebijakan pemerintah .